Target strength of fish based on echogram - Syazrina, Ahmad Safawi (2012)
The purpose of this project is to determine the target strength (TS) of fish based on echogram using the Furuno FQ-80 analyzer. The data collected is the value of TS for ikan kembung (restrelliger kanagurta) and ikan selar boops (ox-eye scad) which is in low frequency data that is 38 kHz. TS value on fish is different according to their types and size. Using the MATLAB software, TS value for fish also can be determined according to its color component. From the ping numbers and the depth of the sea, the position and the TS value on echogram can be determined. The TS value for ikan selar boops (ox-eye scad) is -44.486 and the TS value for ikan kembung (restrelliger Kanagurta) is -54.13. Ikan kembung has the lower TS value than the ikan selar boops.